Association Between Initial Oral Therapy and Outcomes in Systemic Sclerosis–Related Pulmonary Arterial Hypertension. Issue 3 (March 2016) - Lammi, Matthew R.; Mathai, Stephen C.; Saketkoo, Lesley Ann; Domsic, Robyn T.; Bojanowski, Christine; Furst, Daniel E.; Steen, Virginia D.; ,
Abstract : Objective: To compare time to clinical worsening (TTCW) based on initial oral therapy for pulmonary arterial hypertension (PAH) in patients with systemic sclerosis (SSc)–related PAH. Methods: Using data from the Pulmonary Hypertension Assessment and Recognition of Outcomes in Scleroderma (PHAROS) registry (a multicenter prospective observational study enrolling SSc patients with incident pulmonary hypertension), we selected patients with group 1 PAH (World Health Organization Clinical Classification system) who received initial therapy (for 6 months) with an endothelin receptor antagonist (ERA), a phosphodiesterase 5 (PDE5) inhibitor, or a combination of these 2 agents (ERA/PDE5 inhibitor). The main outcome was TTCW, defined as the first occurrence of death, PAH‐related hospitalization, lung transplantation, initiation of parenteral prostacyclin treatment, or worsening symptoms. Results: Ninety‐eight patients (24 in the ERA group, 59 in the PDE5 inhibitor group, and 15 in the ERA/PDE5 inhibitor group) were included. No significant differences in the baseline characteristics of the patients were observed. TTCW was significantly worse in patients in the ERA group compared with those in the PDE5 inhibitor group or the ERA/PDE5 inhibitor group. Ten patients (41.6%) in the ERA group died during the 3‐year observation period, compared with 4 patients (6.8%) in the PDE5 inhibitor group and 1 patient (6.7%) in the ERA/PDE5 inhibitor group. Baseline factors that were independently associated with a shorter TTCW were initial treatment with an ERA (hazard ratio [HR] 2.63 [ P = 0.009]), lower diffusing capacity for carbon monoxide (HR 0.69 per 10% of predicted change [ P = 0.04]), and higher pulmonary vascular resistance (HR 1.10 per Wood unit change [ P = 0.007]). Conclusion: Compared with initial treatment with a PDE5 inhibitor or combination therapy with an ERA and a PDE5 inhibitor, initial therapy with an ERA in patients with SSc‐related PAH was associated with significantly worse TTCW, even after adjustment for commonly accepted prognostic factors. Further study into the optimal initial oral therapy for patients with SSc‐related PAH is needed.